The Study of Coral Recruitment on Artificial Reefs in The Coastal Waters of Penyusuk, Bangka District - Maulana, Eka; Supratman, Okto; Muftiadi, M. Rizza (Coastal and Marine Journal, 2024)
Artificial coral reefs are one of the efforts to rehabilitate resources and serve as a nursery area, providing a permanent new habitat for sessile biota and maintaining the balance of the food chain cycle. This study aims to identify the types of coral attached to artificial reefs and analyze the coral density value on artificial reefs in the waters of Penyusuk Belinyu, Bangka District. Data collection was conducted by counting the number of individuals of coral genera and their sizes visible through the visual census method. The corals found consist of 3 families and 3 genera of coral: the Subergorgiidae family with the Subergorgia genus, the Carijoidae family with the Carijoa genus, and the Faviidae family with the Favia genus, with a total of 136 individuals found in three observation stations. The coral density values ​​for the 3 stations range between; Subergorgia (0.104-0.677 ind/m2), Carijoa (0.677-1.563 ind/m2), and Favia (0.781-1.146 ind/m2). Environmental parameters affecting coral larval settlement include water flow rate, Total Suspended Solids (TSS), temperature, salinity, brightness, and pH.